EDUKASI “ISI PIRINGKU” UNTUK BALITA DI PAUD AL-AZMI KECAMATAN CILAWU GARUT - tri, Tri Wahyuni; desy, Desy Syswianti; Esa, Esa Risi Suazini; Titi, Titi Purwitasari Handayani; Lina, Lina Humaeroh; Linda, Linda; Intan, Intan Syifa (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
The percentage of stunting in Indonesia as a whole is still relatively high and requires special attention. Even though the national stunting rate has decreased from 37.2% in 2013 to 30.8% in 2018, this figure is still below the WHO recommendation of <20%. Mother's knowledge about nutrition will affect the dishes and quality of food served to family members, including toddlers. Lack of maternal knowledge is closely related to the problem of malnutrition which can be seen from the existence of wrong habits in fulfilling toddler nutrition. The "Fill My Plate" movement is a program of the Indonesian Ministry of Health to replace the slogan "4 healthy 5 perfect" as a guideline for daily food to achieve good nutritional status. This service activity aims to provide education about "Fill My Plate " to parents of toddlers. The activity method is carried out in the form of providing education for parents about "Fill My Plate " for toddlers. The activity was held at the Al-Azmi Early Childhood Education, Cilawu District, Garut Regency on Thursday, 03 November 2022 and was attended by 26 participants. The knowledge of parents of toddlers increases after being given education about "Fill My Plate" for toddlers